Sizing and optimization of a hybrid photovoltaic-grid system: application to the port of ghazaouet (algeria) - Fatiha Lassouani; Djamila Kherbouche; Amina Ghomri; Imene Lafri (International Journal of Computational and Experimental Science and Engineering, 2026)
This study presents the sizing and techno-economic optimization of a hybrid photovoltaic (PV)-grid system designed for the port of Ghazaouet located in the Tlemcen province Algeria. The main objective is to assess the technical energy and environmental feasibility of integrating photovoltaic energy to reduce dependence on the conventional electrical grid and fossil fuels. The methodological approach involves analyzing local solar potential detailed assessment of the site’s energy needs and systematic sizing of system components including the photovoltaic array battery storage system charge controller and inverter. A techno-economic simulation and optimization were subsequently performed using HOMER Pro software enabling comparison of several hybrid configurations and identification of the most cost-effective solution based on life-cycle cost. The results indicate a total annual production of approximately 64207 kWh of which 98.9% is provided by photovoltaic energy confirming the dominant role of solar energy. This study demonstrates that hybrid PV-grid systems significantly reduce CO₂ emissions while ensuring a reliable and continuous power supply confirming their relevance as a sustainable solution for industrial zones in Algeria.